Pubic Hair Shaving Is Correlated to Vulvar Dysplasia and Inflammation: A Case-Control Study. (27th August 2017) - Schild-Suhren, Meike; Soliman, Amr A.; Malik, Eduard
Abstract : Objective . The risk factors for vulvar dysplasia and infections are not fully known. In this study, we aimed to investigate the correlation between pubic hair shaving and the occurrence of vulvar inflammation, dysplasia, and cancer. Methods . This study was performed between January 2013 and December 2016 in which a standardized questionnaire concerning genital hair shaving was administered to vulvar dysplasia and cancer patients and healthy participants. The presence of human papilloma virus (HPV) infection and the occurrence of genital inflammation were documented. Results . We recruited 49 patients with vulvar dysplasia or cancer and 234 healthy women as a control group. Smoking, HPV infection, genital inflammation, and complete pubic hair removal were significantly more common in the vulvar dysplasia/cancer group. Pubic hair shaving per se presented a clear association with vulvar dysplasia/cancer. Shaving the labia majora in particular showed also an association. Conclusion . Our findings suggest that partial or complete pubic hair shaving using a razor is correlated with and could be a potential risk factor for the development of genital inflammation, vulvar dysplasia, and malignancies. These results need to be confirmed in larger studies. HPV status and genital inflammation should be documented by medical personnel.